Active Cooling of a Microvascular Shape Memory Alloy‐Polymer Matrix Composite Hybrid Material2 . Issue 7 (29th March 2016) - Coppola, Anthony M.; Hu, Liangfa; Thakre, Piyush R.; Radovic, Miladin; Karaman, Ibrahim; Sottos, Nancy R.; White, Scott R.
Abstract : Microvascular shape memory alloy (SMA)‐polymer matrix composite (PMC) hybrid materials are fabricated using the Vaporization of Sacrificial Components (VaSC) technique. Two types of sacrificial materials are used: Mg wires in the SMA (nickel titanium) and poly(lactic acid)/tin(II) oxalate fibers in the PMC (glass fiber/epoxy). These sacrificial materials survive the initial solidification of the host materials, then are vaporized during a final thermal treatment to reveal the vascular network. The effect of VaSC on composition and transformation temperatures of the SMA are examined. Active cooling through the vascular network maintains temperature in the PMC below the glass transition temperature (152 °C) at heat fluxes as high as 300 kW m −2, while this temperature is exceeded without cooling at just 10 kW m −2 . Abstract : A vascularized hybrid material containing shape memory alloy (SMA) and polymer matrix composite (PMC) hybrid is fabricated by the Vaporization of Sacrificial Components (VaSC) technique. Channels are revealed by embedding a sacrificial template during material production then removal of the template during thermal treatment. Active cooling through the vascular network is demonstrated.